Seminal SIRT1 expression in infertile oligoasthenoteratozoospermic men with varicocoele. (22nd January 2018) - Mostafa, T.; Nabil, N.; Rashed, L.; Makeen, K.; El‐Kasas, M. A.; Mohamaed, H. A.
Summary: In a case‐controlled study, we assessed the expressed seminal NAD‐dependent protein deacetylase (SIRT1) expression in infertile oligoasthenoteratozoospermic (OAT) men associated with varicocoele. Our study involved 81 men, recruited from the University hospitals, after ethical approval and informed consent. They were allocated into fertile normozoospermic men ( n  = 23), infertile OAT men without varicocoele ( n  = 23) and infertile OAT men with varicocoele ( n  = 35). Inclusion criteria consisted of confirmation of abnormal semen parameters and normal female partners whereas exclusion criteria were leukocytospermia, tobacco smoking, hormonal therapy, immunological disorders, dyslipidemia, hypogonadism, cardiovascular disorders, morbid obesity, and hepatic or renal failures. All participants had an interview to assess clinical history, clinical examination, semen analysis, and estimation of seminal SIRT1 expression. Seminal SIRT1 expression was significantly lower in infertile OAT men than fertile men. Among infertile OAT men, seminal SIRT1 expression was significantly lower in those with varicocoele than in those without. Additionally, seminal SIRT1 expression was significantly lower in varicocoele grade III cases compared with other grades. Seminal SIRT1 expression was positively correlated with sperm concentration ( r  = 0.327, p  = 0.001), total sperm motility ( r  = 0.532, p  = 0.001), and sperm normal forms ( r  = 0.469, p  = 0.001). Our results suggest that seminal SIRT1 expression has a role of male infertility being significantly decreased in infertile OAT men in general and in infertile OAT men associated with varicocoele in particular.